The Bible made impossible : why biblicism is not a truly evangelical reading of Scripture - Smith, Christian, 1960- (Grand Rapids, Mich. : Brazos Press, 2012)
Biblicism, an approach to the Bible common among some American evangelicals, emphasizes together the Bible's exclusive authority, infallibility, clarity, self-sufficiency, internal consistency, self-evident meaning, and universal applicability. Sociologist Christian Smith argues that this approach is misguided and unable to live up to its own claims. If evangelical biblicism worked as its proponents say it should, there would not be the vast variety of interpretive differences that biblicists themselves reach when they actually read and interpret the Bible. Smith describes the assumptions, beliefs, and practices of evangelical biblicism and sets it in historical, sociological, and philosophical context. He explains why it is an impossible approach to the Bible as an authority and provides constructive alternative approaches to help evangelicals be more honest and faithful in reading the Bible.
Biblicism and the problem of pervasive interpretive pluralism -- The extent and source of pervasive interpretive pluralism -- Some relevant history, sociology, and psychology -- Subsidiary problems with biblicism -- The Christocentric hermeneutical key -- Accepting complexity and ambiguity -- Rethinking human knowledge, authority, and understanding.
Includes bibliographical references (p. 199-231) and index.
Keywords: Bible -- Evidences, authority, etc; Bible -- Hermeneutics; Evangelicalism